The Effect of Self-Efficacy, Academic Stress, and Academic Fatigue on Students' Learning Outcomes - Firman Firman; Robi Hendra; Ragil Prastian; Fidhiya Marlan Utami; Budi Setiawan (International Journal of Pedagogy and Teacher Education, 2025)
This study investigates the influence of self-efficacy, academic stress, and academic fatigue on the learning outcomes of students at the University of Jambi. Using a quantitative survey method, data were collected via an online questionnaire distributed to 200 randomly selected students from various faculties. The results indicate that self-efficacy positively affects learning outcomes, while academic stress and academic fatigue have negative effects. The structural model shows significant relationships between academic burnout and learning outcomes (β = 0.698, p < 0.001), academic stress and learning outcomes (β = 0.167, p < 0.001), and self-efficacy and academic stress (β = 0.300, p < 0.001). These findings suggest that students with higher self-efficacy are more capable of managing their time, seeking assistance, and maintaining a positive approach to their studies—skills that help them cope with academic pressures and reduce stress. The study underscores the importance of developing interventions to enhance self-efficacy and reduce academic stress and fatigue, such as psychological counseling, stress management programs, and academic support services. These efforts are essential for improving student performance and well-being. The findings are expected to inform the development of educational programs and student welfare policies at the University of Jambi through strategic institutional planning and policy refinement.